ABDALA, a preventive vaccine against SARS-CoV-2, is safe in Chlorocebus aethiops sabaeus monkeys - Lizet Aldana; Iliana Sosa; Juan Carlos Polo; Mariby Gutierrez; Viviana Falcón; Avelina León; Rebeca Castillo; Pedro Puente; Nancy Esteves; Rodolfo Valdés; Marta Ayala; Miladys Limonta; et al. (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2023)
Background: The ABDALA vaccine is a subunit vaccine developed for preventing SARS-CoV-2 infection and the progression of COVID-19 to severe forms, using as an active pharmaceutical ingredient a recombinant version of the SARS-CoV-2 spike protein receptor-binding domain (RBD) expressed in Pichia pastoris. The aim of the paper was to describe the safety profile of the ABDALA vaccine in monkeys (Cholorocebus aethiops sabaeus). For such aim, the vaccine was administered to the monkeys intramuscularly six times every 14 days, following the same scheme used in clinical trials done against COVID-19. Animals were allocated to four groups: Placebo, ABDALA Low-dose (50 µg per animal), ABDALA High-dose (100 µg per animal), and Reversion (100 µg per animal) to be submitted to a clinical, hematological and serum biochemical evaluation. Histopathological assessment of all tissues and organs was also conducted.  Results: As the main results, all animals survived and negative effects were not detected during animal clinical evaluations. The body weight and rectal temperature exhibited no variations and hematological and serum biochemical parameters showed no alterations associated with ABDALA administration. Finally, the histopathological study confirmed the proliferation of spleen white pulp due to ABDALA administration.  Conclusions: Therefore, results strongly suggest ABDALA does not cause toxic effects or damage in the organs of Chlorocebus aethiops sabaeus monkeys, indicating that it is a promising and safe novel vaccine to prevent SARS-CoV-2 infection in humans and the progression of COVID-19 to severe forms.